2012
DOI: 10.3390/ijms131012487
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence Intermittency from Single Quantum Dots to Organic Molecules: Emerging Themes

Abstract: Recent experimental and theoretical studies of photoluminescence intermittency (PI) or “blinking” exhibited by single core/shell quantum dots and single organic luminophores are reviewed. For quantum dots, a discussion of early models describing the origin of PI in these materials and recent challenges to these models are presented. For organic luminophores the role of electron transfer, proton transfer and other photophysical processes in PI are discussed. Finally, new experimental and data analysis methods a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 125 publications
5
37
0
Order By: Relevance
“…1,2 At the single molecule level, the fluorescence emission of these structures fluctuates in intensity but a complete dark state is never reached. Even if blinking properties of nanocrystals (NCs) are complex phenomena 3,4 that cannot be solely explained by a fast Auger recombination in charged NCs 5 and may involve multiple recombination centers, 6,7 it was shown that the blinking inhibition in CdSe/CdS NCs resulted from a reduction of the Auger recombination efficiency. While in regular CdSe/ZnS NCs the Auger lifetime scales as the volume of the emitter and is usually of the order of 10-100 ps, 8,9 in the case of thick-shell CdSe/CdS NCs, Auger lifetimes in the range of tens of nanoseconds have been measured.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 At the single molecule level, the fluorescence emission of these structures fluctuates in intensity but a complete dark state is never reached. Even if blinking properties of nanocrystals (NCs) are complex phenomena 3,4 that cannot be solely explained by a fast Auger recombination in charged NCs 5 and may involve multiple recombination centers, 6,7 it was shown that the blinking inhibition in CdSe/CdS NCs resulted from a reduction of the Auger recombination efficiency. While in regular CdSe/ZnS NCs the Auger lifetime scales as the volume of the emitter and is usually of the order of 10-100 ps, 8,9 in the case of thick-shell CdSe/CdS NCs, Auger lifetimes in the range of tens of nanoseconds have been measured.…”
Section: Introductionmentioning
confidence: 99%
“…Blinking dynamics are commonly investigated by analysis of the probability of a certain length of on‐ and off‐times during a blinking time trace by setting an intensity threshold between PL on‐ and off‐intensities . The general finding is that the probabilities for both times can be tentatively described by a power law often truncated by an exponential cut‐off as described for on‐times in Equation . Pontonα·exptrue(Γnormalonormalntnormalonormalntrue) …”
Section: Resultsmentioning
confidence: 99%
“…Intermittency or blinking of luminescence intensities of single quantum objects such as semiconductor quantum dots (QDs), dye molecules, fluorescent proteins, and color centers is a commonly observed phenomenon . Surprisingly, the time scale of these phenomena covers several orders of magnitude from microseconds to hours for one and the same quantum object.…”
Section: Introductionmentioning
confidence: 99%
“…Their long lifetimes (on the order of 10–40 ns) increase the probability of absorption at shorter wavelengths and produce a broad absorption spectrum. Furthermore, QD emission wavelengths are size‐tunable , and researchers have shown enormous interest in and focus on the synthesis , photophysical property characterization , and bioconjugation of QDs .…”
Section: Ce Separations Of Nanomaterialsmentioning
confidence: 99%